Involvement of the Circadian Rhythm and Inflammatory Cytokines in the Pathogenesis of Rheumatoid Arthritis. (8th May 2014) - Yoshida, Kohsuke; Hashimoto, Teppei; Sakai, Yoshitada; Hashiramoto, Akira
Abstract : Among the symptoms of patients with rheumatoid arthritis (RA), joint stiffness is influenced by diurnal rhythm and reaches peak in the morning, which is a common complaint and reflects the circadian nature of disease manifestation. In addition, inflammatory cytokines, which reach peak secretion early in the morning are major players causing the morning stiffness. In this review, we explore the link between the circadian clock and inflammation, focusing on the interactions of various clock genes with the immune-pathways underlying the pathology of rheumatoid arthritis.